DEFENSE KLUB INDONESIA DI MIKASA THAILAND BASKETBALL SUPER LEAGUE TAHUN 2020 - Siantoro, Gigih; Ramadhan, Bahtiar (Universitas Negeri Surabaya, 2020)
In basketball, the use of statistics seems to be a necessity. The world basketball federation (FIBA) provides statistics on matches around the world that can be accessed through their official website. Although match statistics have a very important role, there are still many coaches, players and clubs in Indonesia who do not fully understand the importance of match statistics in determining the effectiveness of the basketball game.This study examines the effectiveness of the game from the CLS KNIGHTS BBM team in the Thailand Basketball Super League (TBSL) 2020 based on match statistics using descriptive quantitative methods using secondary data obtained from the official Thailand Basketball Super League (TBSL) 2020 website. The results of this study indicate that the CLS KNIGHTS BBM team has different statistical component results in each match. From the results of the calculation of the effectiveness of the game, BBM CLS KNIGHTS has the best record and plays the most effective against BRUNEI PEGASUS (BRN).